The development of hostplant resistance to insect pests: outlook for the tropics - Bosque Pérez, N.A.; Buddenhagen, I.W. (1992)
Host-plant resistance (HPR) to insect pests is considered one of the key tactics for insect control, particularly in developing countries where utilization of other control methods such as pesticides is often difficult or unwise. The search for more sustainable methods of pest control, make host-plant resistance more attractive every day. Additionally, the opportunity for utilizing new insect resistance genes and the ability to move these across plant species, through plant biotechnology, open new doors to the field of HPR. Pest/host-plant complexes are dynamic systems influenced by numerous factors and the development of pest control strategies has to take these into consideration. Major changes in the pest complex of various tropical crops have occurred in recent years as a result of among others: the accidental introduction of new pests or the emergence of new biotypes that make previously resistant varieties ineffective, the introduction of new agronomic practices, and the deployment of new varieties with hidden susceptibility to previously minor pests. Analysis of the origin of crops and their pests is, thus, essential for devising pest control strategies and it is important to have flexible breeding programs that allow for the incorporation of new objectives as new pests come along. There is also a need to breed for varieties with durable resistance, particularly in countries where farmers cannot afford failure of HPR.